E-Money dalam Kordinasi Pengawasan antara Bank Indonesia dan OJK - Cinthya Puspita Shara (DE LEGA LATA: JURNAL ILMU HUKUM, 2021)
It is necessary to know about the Position, Supervision and Cooperation between Bank Indonesia (BI) and the Otoritas Jasa Keuangan (OJK) on Electronic Money Issuers (E-Money issuers). OJK issues E-Money in the form of Banks and Non-Bank Financial Industries. OJK's supervision of E-Money Issuers by Financial Services Institutions is carried out under the authority of the OJK as supervisor, in order to encourage the two institutions to participate in supporting economic growth and maintaining monetary stability. Coordination between OJK and BI in the supervision of E-Money Issuers, namely, BI has the authority to grant licenses to become Electronic Money Issuers and OJK has the authority to supervise Electronic Money Issuers in the form of Banks and the Non-Bank Financial Industry. If the issuance is carried out by a Non-Financial Service Institution, BI shall supervise the issuance and electronic money as the payment system supervisory agency. Based on this research it can be seen that OJK should make a Financial Services Authority Regulation (POJK) that specifically regulates Electronic Money Issuers. BI should not use the term Non-Bank Institution (LSB) because it is considered inaccurate, can cause confusion, and can lead to different understandings.